Cell death regulates muscle fiber number - Sarkissian, Tatevik (Dev Biol, 2016)
Cell death can have both cell autonomous and non-autonomous roles in normal development. Previous studies have shown that the central cell death regulators grim and reaper are required for the developmentally important elimination of stem cells and neurons in the developing central nervous system (CNS). Here we show that cell death in the nervous system is also required for normal muscle development. In the absence of grim and reaper, there is an increase in the number of fibers in the ventral abdominal muscles in the Drosophila adult. This phenotype can be partially recapitulated by inhibition of cell death specifically in the CNS, indicating a non-autonomous role for neuronal death in limiting muscle fiber number. We also show that FGFs produced in the cell death defective nervous system are required for the increase in muscle fiber number. Cell death in the muscle lineage during pupal stages also plays a role in specifying fiber number. Our work suggests that FGFs from the CNS act as a survival signal for muscle FCs. Thus, proper muscle fiber specification requires cell death in both the nervous system and in the developing muscle itself.